RANCANG BANGUN BIBLIOGRAFI BERANOTASI DEBUS BANTEN - feranisa, fara; Sukaesih, Sukaesih; erwina, wina (Jurnal Kajian Informasi dan Perpustakaan, 2017)
ABSTRACT This study about designing of  annotated bibliography Debus Banten used documentation activity step. The purpose of this study is to identifying elements of Debus culture, collecting information resources of Debus culture, knowing standard of cataloguing rules in Indonesia now, knowing classification type that commonly used to bibliography, knowing the rules of abstract for support manufacture of bibliography of  Debus. The method used is action research, with designing of annotated bibliography of Debus. Data collecting technique used is observation, informal interviews, and publicities literature. The result of this study that in designing a bibliography of Debus is identifying Debus, collecting information resources related to Debus. After that designing a bibliography using the standard rules of bibliography in national library Republik Indonesia now, is DDC 23 (classification) and AACR2 (cataloguing). This study is resulting a secondary documents is bibliography of Debus Banten. Bibliography of Debus has been tested public to student of faculty of Adab dan Humanities UIN Syarif Hidayatullah and the result is positif, bibliography of Debus can be used by information seekers.